(a+b)(3b+1)
6
12ab+3ab=15ab
It is an algebraic expression because it has no equality sign.
GCF(6a2bx, 15ab2x-24ab) = GCF[6a2bx, 3ab(5bx-8)] = 3ab
(3a - 2c)(b - d)
To factor the expression 3ab + 3ac + 2b^2 + 2bc, we first look for common factors among the terms. We can factor out a 3a from the first two terms, and a 2 from the last two terms. This gives us 3a(b + c) + 2(b^2 + bc). Next, we notice that we can factor out a b from the second term in the second parenthesis, giving us the final factored form: 3a(b + c) + 2b(b + c).
(a+b)(3b+1)
(3b - 1)(a - b)
6
12ab+3ab=15ab
(3b - 1)(a - b)
Factorizing 3ab + 3ac gives 3a (b + c).Factorizing is to express a number or expression as a product of factors.When factorizing always look for common factors. To factorize (3ab + 3ac) look for the highest factor between the two terms (3a). 3ab + 3ac = 3a (b + c)
3ab - a - 3b2 + b = -3b2 + 3ab + b - a = -3b(b - a) + 1(b - a) = (1 - 3b)(b - a)
3ab[35 - 4]
It is: 3ab
-2ab